Respuesta :

Answer 1: Move the -7 over to the right side of the problem.
Answer 2: [tex]x^2 + 6x + 9 = 7+9[/tex]
Answer 3: [tex](x+3)^2 = 16[/tex]
Answer 4: Use the square root for both sides of the equation.
Answer 5: x = -3 ± 4 = 1, -7 --> x = 1, -7

Answer:

Answer 1: Move the -7 over to the right side of the problem.

Answer 2: x^2 + 6x + 9 = 7+9

Answer 3: (x+3)^2 = 16

Answer 4: Use the square root for both sides of the equation.

Answer 5: x = -3 ± 4 = 1, -7 --> x = 1, -7

Step-by-step explanation:

ACCESS MORE